(Im)pure bodies and the Body of Christ: Judith Butler and Bruno Latour on (im)purity and the implications for contemporary Eucharistic participation. Issue 1 (1st January 2023) - Harper, Whitney
ABSTRACT: Recent discussions about Eucharistic practice in the United States have received increased public attention with stories of pro-life politicians being excluded from participation. In this practice of exclusion, there is a depiction of protecting the Eucharist from impurity, with the priests citing the pro-life framework as the basis for inclusion. Using this site for reflection, this article seeks to interrogate these representations of (im)purity specifically with reference to the abortion debate and the Eucharist. Taking the concept of impurity found in the works of Judith Butler and Bruno Latour and placing it in conversation with 'purity culture' and the disproportional focus on bodies of women in cases of abortion, I seek to address constructed boundaries between dualisms such as pure and impure, as well as Church and the world. More specifically, I aim to reconfigure impurity away from being an 'evil that must be avoided' (Thomas Bauer) by the Church and instead ask how this can serve as a rich resource for scholars reflecting on religious practices today, rethinking the Body of Christ as one of inherent interdependency and porosity – not a space in need of protection from 'impurity', but one that further divides representations of purity and impurity altogether.